(untitled) - Wildman, Jayne (Oxford, 2003)
This book is for young adults developing English language skills. It provides practice and exercises to improve vocabulary, grammar and writing skills, and includes speaking and listening tasks. The multi-syllabus approach uses up-to-date topics for teenage students to read and discuss
Keywords: English language; Textbooks for foreign speakers